The limitation of optical equipment in New Crescent Moon visibility: insight from 27 years of observation data in Sarawak, Malaysia - Ahmad Hariz Bely; Roslan Umar; Nor Hazmin Sabri; Ahmad Lutfi Afifi Mohd Nasir; Razalie Hussaini; Emma Zulaiha Zulkifli; Amirul Akmal Redzuan; Rakhmadi, Arwin Juli; Amirul Hazim Kamarulzaman; Che Ku Ahmad Fuad Che Ku Abdullah; Nur Azhar Ahmad; Nur Zulaikha Mohd Afandi; et al. (Penerbit Universiti Kebangsaan Malaysia, 2025)
New Crescent Moon visibility has been extensively studied throughout history due to its undeniable importance in determining the Islamic calendar. Previous visibility models have relied on linear statistical theory, which does not fully account for the circular nature of the variables involved such as atmospheric turbulence, light pollution and limitations of optical equipment. In order to address this matter, this study proposed a new visibility using the limitation of New Crescent Moon sighting via an optical equipment. Data were categorized into two visibility categories, namely: visible to the theodolite and potentially requiring telescopes based on the night visibility that has been captured. The categorization is determined based on the residual local data observations collected in Sarawak, spanning from 1997 to 2023. The proposed limitation was applied by 31 positive data from 167 observations which results indicate that the visibility based on moon ages and altitude of the moon features parameter. This study suggested that the limitation of sighting the New Crescent Moon using an optical equipment range between 11 and 13 h of moon age with a moon altitude of 5° and 6°. These new criteria have a significant positive impact on enhancing the likelihood of observing the New Crescent Moon and improving the accuracy of the Islamic calendar especially in Sarawak.